(√x - 1)^2/x=
=(x - 2·√x + 1)/x =
=- 2/√x + 1/x + 1
∫(2/√x)dx =
=4·√x
∫(1/x) dx = LN(x)
∫ 1 dx = x
Quindi:
∫((√x - 1)^2/x) dx =
= LN(x) + x - 4·√x
Valutato in x = 4:
LN(4) + 4 - 4·√4
Valutato in x = 1:
LN(1) + 1 - 4·√1 = -3
Quindi:
LN(4) + 4 - 4·√4 + 3 = 2·LN(2) - 1
∫[x + 1 - 2 radice(x)] / x dx =
=∫(x / x) dx + ∫(1/x) dx - 2∫ [radice(x) / x] dx =
= ∫1 * dx + ∫(1/x) dx - 2 ∫ radice(x/x^2) dx calcolati tra 1 e 4
∫1 dx = x ; tra 1 e 4;
∫(1/x) dx = ln(x) ; tra 1 e 4;
- 2 ∫ radice(x/x^2) dx = - 2 ∫radice(1/x) dx = - 2 ∫ [(x^-1)^1/2 dx =
= - 2 ∫ (x^-1/2) dx = - 2 * (x^1/2) / (1/2) = - 2 * 2 radice(x); tra 1 e 4;
∫[x + 1 - 2 radice(x)] / x dx = x + lnx - 4 radice(x) =
= 4 - 1 + ln(4) - ln(1) - 4 * [radice(4) - radice(1)] =
= 3 + ln(2^2) - 0 - 4 * (2 - 1) =
= 3 + 2 ln(2) - 4 * 1 = 2 ln(2) - 4 + 3 = 2 ln(2) - 1.
Ciao @alby